Konsumsi dalam Perspektif Ekonomi Islam (Regresi Religiusitas terhadap Konsumerisme pada Mahasiswa UIN Syarif Hidayatullah Jakarta) - Herlina Yustati (JURNAL INDO-ISLAMIKA, 2015)
This article discusses how the understanding and application of the religion have an influence on individual behavior in terms of consumption behavior. This article proves that a good understanding of religion and it application will bring a good consumption behavior. Good consumption behavior is the behavior of consumption away from the hedonistic lifestyle and extravagant and consumption behavior which only buy what is needed and not buy what is desired. This article also shows that who has a higher the level of religiosity (religious understanding and it application) will have the lower level of consumerism (buying behavior are considered luxury items is a measure of happiness), this is evidenced by the t value is negative.